Archeologia Pubblica in Toscana Un progetto e una proposta - VANNINI, Guido (Strumenti per la didattica e la ricerca, 2011)
Can archaeology be considered a factor of socio-economic development for civil society? This, in short, is the question underlying the first national workshop devoted to Public Archaeology (Archeologia Pubblica in Toscana: un progetto e una proposta, Aula Magna, 12 July 2010), organised by the Chair of Mediaeval Archaeology of the University of Florence with the collaboration of the Universities of Pisa and Siena. The meeting also provided the opportunity to communicate the socio-economic results of a case study of projects that the Tuscan universities have recently successfully developed in this sector, involving local authorities, museums, public and private enterprises in forms of active partnership. Public archaeology is seen as the updating of the original vocation of the discipline to address the contemporary, in terms of economics, governance, communication, identity of the archaeological assets and the respective social communities.